The Fair and Responsible Use of Space An International Perspective - Rathgeber, Wolfgang; Schrogl, Kai-Uwe; Williamson, Ray A. (Studies in Space Policy, 2010)
As space applications become central to modern interaction, more and more entities are becoming involved in space activities. Consequently, strategies to establish the coordinated, ethically justifiable and sustainable conduct of space activities have to be found. Such an endeavour requires addressing current questions regarding the use of space, dealing with fair rules in orbit and discussing the way towards achieving truly global engagement on space security issues. The book outlines the current situation and identifies key challenges from the policy perspective. Taking this one step further, it also formulates principles and recommendations for global action. Nineteen eminent personalities from the space sector have united for this project, which is based on a conference organised at the European Space Policy Institute (ESPI) in November 2008 in Vienna.